ZmPP2C26 Alternative Splicing Variants Negatively Regulate Drought Tolerance in Maize - Lu, Fengzhong; Li, Wanchen; Peng, Yalin; Cao, Yang; Qu, Jingtao; Sun, Fuai; Yang, Qingqing; Lu, Yanli; Zhang, Xuehai; Zheng, Lanjie; Fu, Fengling; Yu, Haoqiang (Frontiers in Plant Science, 2022)
Serine/threonine protein phosphatase 2C (PP2C) dephosphorylates proteins and plays crucial roles in plant growth, development and stress response. Here, we characterized a clade B member of maize PP2C family, ZmPP2C26, that negatively regulated drought tolerance by dephosphorylating ZmMAPK3 and ZmMAPK7 in maize. The ZmPP2C26 gene generated ZmPP2C26L and ZmPP2C26S isoforms through untypical alternative splicing. ZmPP2C26S lost 71 amino acids including a MAPK interaction motif and showed higher phosphatase activity than ZmPP2C26L. ZmPP2C26L directly interacted with, dephosphorylated ZmMAPK3 and ZmMAPK7, and localized in chloroplast and nucleus, but ZmPP2C26S only dephosphorylated ZmMAPK3 and localized in cytosol and nucleus. The expression of ZmPP2C26L and ZmPP2C26 was significantly inhibited by drought stress. Meanwhile, the maize zmpp2c26 mutant exhibited enhancement of drought tolerance with higher root length, root weight, chlorophyll content and photosynthetic rate compared to wild type. However, overexpression of ZmPP2C26L and ZmPP2C26S significantly decreased drought tolerance in Arabidopsis and rice with lower root length, chlorophyll content and photosynthetic rate. Phosphoproteomic analysis revealed that the ZmPP2C26 protein also altered phosphorylation level of proteins involved in photosynthesis. The study provides insights into understanding the mechanism of PP2C in response to abiotic stress.